Multi-component thermoplastic products

By introducing degraded enzymes and low conversion temperature plastic materials into multi-component plastic products, the problem of slow degradation of plastic products is solved, and rapid partial degradation under environmental conditions and the maintenance of enzyme activity after heat treatment is achieved. It is suitable for a variety of plastic products.

JP7628501B2Active Publication Date: 2025-02-10キャルビオス
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021557208
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-28
Filing Date
2020-03-27
Publication Date
2025-02-10
Estimated Expiration
2040-03-27

AI Technical Summary

Technical Problem

The biodegradation rate of existing plastic products is slow and incomplete, resulting in serious environmental pollution problems, especially the single-use plastic products are difficult to quickly decompose in the natural environment.

Method used

A multi-component plastic product is developed in which one plastic material contains a degradation enzyme and the other plastic material has a conversion temperature lower than the target material. Through coextrusion or co-injection molding processes, the degradation enzyme can effectively degrade adjacent plastic materials.

Benefits of technology

It realizes rapid partial degradation of plastic products under environmental conditions, reduces environmental pollution, and the degradation enzymes remain active during heat treatment. It is suitable for a variety of plastic products such as multi-layer films, plastic bottles and packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628501000001
    Figure 0007628501000001
  • Figure 0007628501000002
    Figure 0007628501000002
  • Figure 0007628501000003
    Figure 0007628501000003
Patent Text Reader

Abstract

The present invention relates to a multi-component plastic product comprising at least two different thermoplastic materials, wherein a first thermoplastic material comprises a first thermoplastic polymer and a second thermoplastic material comprises at least one second thermoplastic polymer and at least one degrading enzyme capable of degrading the first thermoplastic polymer, the second thermoplastic material having a transformation temperature (Tf) lower than the transformation temperature (Tf) of the first thermoplastic material, and wherein the first and second plastic materials are at least partially adjacent in the multi-component product.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multi-component thermoplastic product. More particularly, the present invention relates to a multi-component product comprising at least two distinct polymeric regions, one of which contains a degrading enzyme suitable for degrading at least one polymer of another polymeric region. The present invention also relates to a method for producing the multi-component plastic product. [Background technology]

[0002] Plastics are cheap, durable materials that can be used to manufacture a wide variety of products used in a wide range of applications, and as such, the production of plastics has increased dramatically over the past few decades.

[0003] Multicomponent plastic products, such as multicomponent filaments and multi-layer plastics, are often used to combine the properties of polymers (i.e. high thermal stability, chemical inertness, density, elasticity, etc.). For example, certain beverage packaging, such as beer bottles and sparkling water, sandwiches a polyvinyl alcohol (PVOH) or polyamide layer with PET to reduce the gas permeability of the package. Similarly, some rigid food packaging, such as food trays, contain a layer of polyethylene (PE) as a welding agent between the tray and lid, both constructed of PET.

[0004] Over 50% of these plastics are used in single-use, disposable applications such as packaging, agricultural films, disposable consumer goods, or in short-lived products that are discarded within one year of production. Due to the durability of the polymers they contain, significant amounts of plastics accumulate in landfills and natural habitats around the world, creating increasing environmental problems. Degradable and even biodegradable plastics can persist for decades depending on local environmental factors such as levels of UV exposure, humidity, temperature, the presence of appropriate microorganisms, etc.

[0005] To address these issues, various physical, chemical and / or biochemical methods have been developed to enhance the biodegradation rate of polymers, resulting in the development of biodegradable plastic products. However, the degradation conditions in the environment are not optimal for such biodegradable plastics, and their degradation is generally partial.

[0006] Recently, new plastic materials have been developed that contain small amounts of biological entities with polymer-degrading activity, as described in WO 2013 / 093355, WO 2016 / 198652 and WO 2016 / 198650. The biological entities are interestingly capable of degrading at least one polymer of the plastic material and are dispersed in the plastic material. The plastic material thus obtained can be directly used to manufacture plastic products with improved biodegradability via an extrusion die. Summary of the Invention

[0007] By working on plastic materials and enzymes to be incorporated therein to promote polymer degradation, the inventors have developed a new plastic product comprising two or more separate plastic materials, composed of different thermoplastic polymers. The first plastic material does not contain a degradative enzyme, whereas the second plastic material contains a degradative enzyme capable of degrading the thermoplastic polymer of the first plastic material. According to the invention, the two or more plastic materials are at least partially adjacent, but not intimately mixed. Indeed, the inventors have surprisingly discovered that physical contact between two adjacent regions allows the degradative enzyme present in one region to degrade the thermoplastic polymer in the adjacent region and eventually spread to this region. The degradative enzyme thereby comes into contact with the first polymer and causes its degradation. The inventors have also developed a method for the manufacture of such a multi-component plastic. Interestingly, the inventors propose to introduce a degradative enzyme into a thermoplastic material having a transformation temperature lower, in particular at least 50° C. lower, than the transformation temperature of the thermoplastic material comprising the polymer targeted by the degradative enzyme. Thus, with the method of the invention it is possible to produce a thermoplastic product comprising a thermoplastic polymer having a high transformation temperature and a degrading enzyme capable of degrading said thermoplastic polymer, in which the enzyme still exhibits a sufficiently efficient degrading activity to allow at least partial degradation of a plastic product.

[0008] In this regard, the object of the present invention is to provide a multicomponent product comprising at least two different thermoplastic materials, the first thermoplastic material comprises a first thermoplastic polymer; the second thermoplastic material comprises at least one second thermoplastic polymer and at least one degrading enzyme capable of degrading the first thermoplastic polymer; The second thermoplastic material has a transformation temperature (Tf) lower than the transformation temperature (Tf) of the first thermoplastic material, and the first plastic material and the second plastic material are at least partially adjacent in the multi-component product.

[0009] According to the present invention, the degradative enzyme is capable of degrading a first thermoplastic polymer in a multi-component plastic product.

[0010] The multi-component product is advantageously selected from multi-component filaments and multi-layer plastic products, including multi-layer plastic films, multi-layer plastic sheets, multi-layer plastic trays, multi-layer plastic bottles, multi-layer packaging, multi-layer profiles and multi-layer tubes.

[0011] The thermal treatment or transformation process or processing step used to produce the multicomponent product is advantageously coextrusion, coinjection or extrusion coating, preferably coextrusion.

[0012] In one particular embodiment, the first thermoplastic polymer is PLA and the second thermoplastic polymer is PCL.

[0013] In another particular embodiment, the first thermoplastic polymer is PET and the second thermoplastic polymer is PCL.

[0014] A further object of the present invention is to a. selecting a first thermoplastic material comprising a first thermoplastic polymer; b. selecting a degrading enzyme capable of degrading the first thermoplastic polymer; c. mixing the degradative enzyme with a second thermoplastic polymer at a temperature at which the second thermoplastic polymer is partially or completely molten to obtain a second thermoplastic material, the second thermoplastic material having a transformation temperature (Tf) lower than the transformation temperature (Tf) of the first thermoplastic material; d. co-extrusion or co-injection or extrusion coating said thermoplastic material to obtain a multi-component product; and (b) providing a method for producing the multi-component product according to the present invention, comprising:

[0015] These and other objects and embodiments of the present invention will become more apparent after a detailed description of the invention, including preferred embodiments thereof, given in general terms. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] definition The present disclosure will be best understood with reference to the following definitions.

[0017] "Thermoplastic material" refers to a composition in the solid or molten state, prior to any shaping or conditioning process, that comprises one or more thermoplastic polymers and optional additional substances or additives, such as plasticizers, inorganic or organic fillers. Preferably, the thermoplastic material comprises a mixture of semi-crystalline and / or amorphous polymers, or a semi-crystalline polymer. In certain embodiments, the thermoplastic material comprises only amorphous thermoplastic polymers (and, optionally, enzymes and / or additives). According to the present invention, the thermoplastic material is used to manufacture plastic products or textiles.

[0018] Within the context of the present invention, the term "multicomponent plastic product" or "multicomponent thermoplastic product" refers to any goods or products (such as plastic sheets, films, tubes, rods, profiles, shapes, blocks, fibers, filaments, threads, etc.) that contain different physically separate regions or parts, some of which are adjacent, each of which contains a different thermoplastic polymer. In the context of the present invention, a multicomponent plastic product encompasses any kind of plastic product that is composed of at least two thermoplastic materials arranged on one another so that they are not intimately mixed. For example, some regions of a multicomponent plastic product may be glued together or naturally bonded together due to the compatibility of the plastic materials or due to the use of additives between the two regions. In particular, multicomponent plastic products are manufactured products such as rigid or flexible packaging, agricultural films, bags, filaments, textiles, nonwovens, disposable goods, etc.

[0019] "Polymer" refers to a compound or mixture of compounds whose structure is composed of multiple repeating units linked by covalent chemical bonds. "Thermoplastic polymer" refers to a polymer that becomes moldable above a certain temperature and solidifies upon cooling. In most cases, a thermoplastic polymer is at least moldable above its melting temperature (Tm). Some thermoplastic polymers begin to become moldable at their glass temperature (Tg). Such temperatures can be estimated by various analytical methods. For example, differential scanning calorimetry (DSC) or differential thermal analysis (DTA) can be used to determine the Tg and Tm of a polymer. Within the context of the present invention, the term thermoplastic polymer includes synthetic thermoplastic polymers composed of a single type of repeating unit (i.e., homopolymers) or a mixture of different repeating units (i.e., copolymers). Synthetic thermoplastic polymers include thermoplastic polymers derived from petroleum or from bio-based materials, such as polyolefins, aliphatic or aromatic polyesters, polyamides, polyurethanes, and vinyl polymers.

[0020] According to the present invention, the term "transformation temperature" (Tf) corresponds to the temperature at which a thermoplastic material is partially or completely in a molten state, i.e. at which it is sufficiently fluid to be processed by extrusion or any thermal treatment. The "transformation temperature", also called "processing temperature", is easily determined by the skilled person, taking into account the production method (i.e. the transformation process) and / or the components of the thermoplastic material, in particular taking into account the Tf of the thermoplastic polymers contained in said thermoplastic material (said Tf being provided in the technical data sheet of the thermoplastic polymer) and / or taking into account the Tf of other thermoplastic materials co-extruded and / or coinjected with said thermoplastic material (e.g. so that both co-extruded and / or coinjected thermoplastic materials obtain a similar viscosity when arriving at a common die). By way of example, the transformation temperature of a thermoplastic material that mainly comprises semi-crystalline polymers is generally close to or higher than the melting temperature (Tm) of said polymer, preferably higher than the Tm of said polymer. For thermoplastic materials that contain primarily amorphous polymers, the transformation temperature refers to the temperature at which the thermoplastic material is sufficiently fluid (i.e., in a rubbery or softened state) to be processed by extrusion or any heat treatment, also called the "softening temperature". Such a temperature is generally higher than the glass transition temperature (Tg) of such amorphous polymer. When a thermoplastic material contains two or more thermoplastic polymers with different Tm (or softening temperatures), the transformation temperature of the thermoplastic material is close to or higher than the Tm (or softening temperature) of the predominant thermoplastic polymer. Alternatively, the transformation temperature of the thermoplastic material is close to or higher than the highest Tm (or highest softening temperature).

[0021] In certain embodiments, the transformation temperature of a thermoplastic material can be adjusted (i.e., increased or decreased compared to the Tf of the thermoplastic polymer of the thermoplastic material itself) by the addition of an additive(s) that can affect the flowability of the polymer.

[0022] As used herein, the term "degradative enzyme" refers to an enzyme having polymer degrading activity. In the context of the present invention, "degradative enzyme" may refer to a pure enzyme or a formulation containing the enzyme(s) and diluent(s) and / or carrier(s), such as stabilizing component(s) and / or solubilizing component(s), including water, glycerol, sorbitol, dextrin, (e.g., maltodextrin and / or cyclodextrin), starch, gum arabic, glycols (e.g., propanediol and monoethylene glycol), salts, etc. The degradative enzyme may be in solid (e.g., powder) or liquid form.

[0023] As used herein, the terms "lower" or "below" a given temperature should be understood as "strictly lower" and "strictly less than," respectively, i.e., not including the given temperature.

[0024] As used herein, the term "by weight" means "based on the total weight" of the composition or product under consideration.

[0025] In the context of the present invention, the term "about" refers to a difference of + / - 5%, preferably + / - 1%, or within the tolerance of an appropriate measuring device or instrument.

[0026] Plastic materials The present invention proposes to use at least two separate thermoplastic materials, each comprising a thermoplastic polymer, to produce a plastic product comprising at least two separate parts, i.e. a multi-component product, where the separate parts or regions are not melted within the plastic product and remain physically separate even if they are directly adjacent.

[0027] According to the invention, each plastic material comprises a thermoplastic polymer, one of which further comprises a degrading enzyme capable of degrading the thermoplastic polymer of another plastic material, the thermoplastic material comprising the degrading enzyme (hereinafter the "second thermoplastic material") having a transformation temperature strictly lower than that of the thermoplastic material (hereinafter the "first thermoplastic material") whose polymer must be degraded by the degrading enzyme.

[0028] In one particular embodiment, the second thermoplastic material has a transformation temperature that is at least 50° C. lower, preferably 60° C., 70° C., 80° C. lower than the transformation temperature of the first thermoplastic material.

[0029] In one particular embodiment, both thermoplastic materials comprise at least 70%, 75%, 80%, 85%, 90%, preferably at least 95% by weight of a semi-crystalline thermoplastic polymer based on the total weight of the polymers in the thermoplastic materials, said semi-crystalline thermoplastic polymer of the second material having a melting temperature (Tm) strictly lower than the melting temperature (Tm) of said semi-crystalline thermoplastic polymer in the first thermoplastic material. Preferably, the semi-crystalline thermoplastic polymer of the second thermoplastic material has a Tm at least 50° C. lower, more preferably 60° C., 70° C., 80° C. lower than the Tm of the semi-crystalline thermoplastic polymer of the first thermoplastic material.

[0030] In one particular embodiment, both thermoplastic materials comprise at least 70%, 75%, 80%, 85%, 90%, preferably at least 95% by weight of amorphous polymer based on the total weight of the polymers in the thermoplastic materials, and the amorphous thermoplastic polymer of the second material has a softening temperature strictly lower than the softening temperature of the amorphous thermoplastic polymer in the first thermoplastic material. Preferably, the amorphous thermoplastic polymer of the second thermoplastic material has a softening temperature at least 50° C. lower, more preferably 60° C., 70° C., 80° C. lower than the softening temperature of the amorphous thermoplastic polymer of the first thermoplastic material.

[0031] In one particular embodiment, both thermoplastic materials comprise a mixture of amorphous and semi-crystalline polymers, with the polymer of the second material having a transformation temperature strictly lower than the transformation temperature of the polymer in the first thermoplastic material, preferably at least 50°C lower, more preferably 60°C, 70°C, 80°C lower.

[0032] It is therefore an object of the present invention to provide a multi-component plastic product comprising at least two different thermoplastic materials, the first thermoplastic material comprising at least 70%, 75%, 80%, 85%, 90%, preferably at least 95% by weight of a first semi-crystalline thermoplastic polymer, based on the total weight of the first thermoplastic material, the second thermoplastic material comprises at least 70%, 75%, 80%, 85%, 90%, preferably at least 95% by weight of a second semi-crystalline thermoplastic polymer based on the total weight of the second thermoplastic material, and at least one degrading enzyme capable of degrading said first semi-crystalline thermoplastic polymer; The second semi-crystalline thermoplastic polymer has a melting temperature (Tm) lower than the melting temperature (Tm) of the first semi-crystalline thermoplastic polymer, and the first thermoplastic material and the second thermoplastic material are at least partially adjacent in the multi-component product.

[0033] In one particular embodiment, the second semi-crystalline thermoplastic polymer has a Tm that is at least 50° C. lower, preferably 60° C., 70° C., 80° C. lower than the Tm of the first semi-crystalline thermoplastic polymer.

[0034] In a preferred embodiment, the thermoplastic polymers used for the two plastic materials are different from each other. For example, the polymer of the first thermoplastic material is PLA and the polymer of the second thermoplastic material is selected from PCL, PBS, PBSA or PBAT, preferably PCL. In another particular embodiment, the polymer of the first thermoplastic material is PET and the polymer of the second thermoplastic material is selected from PCL, PBAT, PBSA, PBS, PBA, PGA, PLA, PLGA, PHA and copolymers thereof. In another embodiment, the polymer of the first thermoplastic material is PET and the polymer of the second thermoplastic material is selected from PET copolymers.

[0035] In another particular embodiment, the polymers of the thermoplastic material are selected from different grades of polymers of the same type (i.e., having the same chemical formula) with different transformation temperatures and / or different melting temperatures. As known to those skilled in the art, the grade of a polymer is defined according to the molecular weight, isomer ratio, branching, etc. of the polymer. The final plastic product will thus be made of a single type of polymer exhibiting different grades. For example, both thermoplastic polymers are PLA, and the first thermoplastic material comprises 4043D PLA grade manufactured by NatureWorks and the second thermoplastic material comprises PLA Luminy LX930 manufactured by Total Corbion.

[0036] In another particular embodiment, the polymers of the thermoplastic materials are selected from the same type and grade of polymers, but the second thermoplastic material further comprises a component (e.g., a plasticizer, a filler, or an additional polymer) that can reduce the viscosity of said polymer, resulting in a reduction in the Tf of the second thermoplastic material compared to the Tf of the first plastic material. For example, both thermoplastic polymers are selected from the same grade of PLA, such as 4043D PLA grade from NatureWorks, but the second thermoplastic material further comprises a plasticizer such that its viscosity is reduced compared to the viscosity of the first thermoplastic material. Such a reduction in the viscosity of the thermoplastic material results in a reduction in its Tf compared to the Tf of the thermoplastic material having a higher viscosity.

[0037] In another embodiment, additives may be added to one or both thermoplastic materials to reduce the viscosity difference between both thermoplastic materials. Such adjustments may be achieved by the addition of plasticizers, fillers, polymer(s) with higher or lower viscosity, or any means known to those skilled in the art for modifying the viscosity of a polymer, including different grades of the same polymer contained in the thermoplastic materials. Such additions may be made during the production of each thermoplastic material or directly during the manufacturing process of the multi-component plastic product.

[0038] First Thermoplastic Material According to the invention, the first plastic material comprises a first thermoplastic polymer and, optionally, additives or fillers. Preferably, the first plastic material comprises at least 70%, 75%, 80%, 85%, 90%, 95%, 99% by weight of the first thermoplastic polymer, based on the total weight of the first plastic material. In one particular embodiment, the first plastic material comprises 100% wt of the first thermoplastic polymer. In another embodiment, the first plastic material comprises two or more thermoplastic polymers, the first thermoplastic polymer (targeted by the degradative enzymes in the second plastic material) representing 70%, 75%, 80%, 85%, 90%, 95% by weight of the first thermoplastic material. In one particular embodiment, said first thermoplastic polymer is a mixture of different grades of polymers of the same type (i.e. having the same chemical formula).

[0039] Advantageously, the first thermoplastic material has a transformation temperature (Tf) above 120° C., preferably above 150° C., more preferably above 180° C. In particular, the first thermoplastic material comprises at least 70%, 75%, 80%, 85%, 90%, preferably at least 95% by weight of a first semi-crystalline thermoplastic polymer, based on the total weight of the first thermoplastic material, said semi-crystalline thermoplastic polymer having a melting temperature (Tm) above 120° C., preferably above 150° C., more preferably above 180° C.

[0040] Preferably, the first thermoplastic polymer is selected from water insoluble polymers.

[0041] Preferably, the first thermoplastic polymer is selected from polyolefins, aliphatic and semi-aromatic polyesters, polyamides, polyurethanes, vinyl polymers, polyether or ester ether copolymers and derivatives thereof, preferably from aliphatic and semi-aromatic polyesters.

[0042] Preferred polyolefins for use in the present invention include, but are not limited to, polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), polybutene-1 (PB-1), polyisobutylene (PIB), cyclic olefin copolymers (COC) and derivatives or blends / mixtures thereof.

[0043] Preferred aliphatic polyesters for use in the present invention include, but are not limited to, polylactic acid (PLA), poly(L-lactic acid) (PLLA), poly(D-lactic acid) (PDLA), poly(D,L-lactic acid) (PDLLA), PLA stereocomplex (scPLA), polyglycolic acid (PGA), polyhydroxyalkanoates (PHAs), polycaprolactone (PCL), polybutylene succinate (PBS), and semi-aromatic polyesters include polyethylene terephthalate (PET), polytrimethylene terephthalate (PT Poly(ethylene glycol) copolymers (PLGA) and their derivatives or blends / mixtures. The polyether may be selected from, for example, polyethylene glycol (PEG), preferably PEG with a molecular weight of more than 600 g / mol, polyethylene oxide (PEO), or their copolymers and blends / mixtures. The ester ether copolymer may be selected from, for example, polydioxanone (PDS).

[0044] Preferred polyamide polymers (also called nylons) for use in the present invention include polyamide-6 or poly(β-caprolactam) or polycaproamide (PA6), polyamide-6,6 or poly(hexamethylene adipamide) (PA6,6), poly(11-aminoundecanoamide) (PA11), polydodecanolactam (PA12), poly(tetramethylene adipamide) (PA4,6), poly(pentamethylene sebacamide) (PA5,10), poly(hexamethylene azelaate) (PA6,11), poly(hexamethylene azelaate) (PA7,12), poly(hexamethylene azelaate) (PA8,13), poly(hexamethylene azelaate) (PA9,14), poly(hexamethylene azelaate) (PA15,16), poly(hexamethylene azelaate) (PA17,17), poly(hexamethylene azelaate) (PA18,19), poly(hexamethylene azelaate) (PA19,20), poly(hexamethylene azelaate) (PA20,21), poly(hexamethylene azelaate) (PA22,23), poly(hexamethylene azelaate) (PA24,25), poly(hexamethylene azelaate) (PA26,26), poly(hexamethylene azelaate) (PA28,27), poly(hexamethylene azelaate) (PA29,30), poly(hexamethylene azelaate) (PA30,31), poly(hexamethylene azelaate) (PA31,32), poly(hexamethylene azelaate) (PA32,33), poly(hexamethylene azelaate) (PA33,34), poly(hexamethylene azelaate) (PA34,35), poly(hexamethylene azelaate) (PA35,36), poly(hexamethylene azelaate) (PA35,37), poly(hexamethylene azelaate) (PA3 Poly(hexamethylene adipamide) (PA6,9), poly(hexamethylene sebacamide) (PA6,10), poly(hexamethylene dodecanoamide) (PA6,12), poly(m-xylylene adipamide) (PAMXD6), polyhexamethylene adipamide / polyhexamethylene terephthalamide copolymer (PA66 / 6T), polyhexamethylene adipamide / polyhexamethylene isophthalamide copolymer (PA66 / 6I) and derivatives or blends / mixtures thereof.

[0045] Preferred vinyl polymers include polystyrene (PS), polyvinyl chloride (PVC), polyvinyl chloride (PVdC), ethylene vinyl acetate (EVA), ethylene vinyl alcohol (EVOH), polyvinyl alcohol (PVOH) and derivatives or blends / mixtures of these materials.

[0046] In one particular embodiment, the first thermoplastic polymer is selected from thermoplastic polymers having a transformation temperature (Tf) above 120° C., preferably above 150° C., more preferably above 180° C., and / or a glass transition temperature (Tg) above 10° C. In another particular embodiment, the first thermoplastic polymer is selected from semi-crystalline polymers having a melting temperature (Tm) above 120° C., preferably above 150° C., more preferably above 180° C., and / or a glass transition temperature (Tg) above 10° C. In another embodiment, the first thermoplastic polymer is selected from amorphous polymers having a softening temperature above 120° C., preferably above 150° C., more preferably above 180° C., and / or a glass temperature (Tg) above 10° C.

[0047] In one particular embodiment, the first thermoplastic polymer is selected from aliphatic polyesters, preferably polylactic acid (PLA).

[0048] In another particular embodiment, the first thermoplastic polymer is selected from semi-aromatic polyesters, preferably polyethylene terephthalate (PET) or its copolymers, such as PET-G (glycolyzed PET) or low melting PET. Alternatively, the first thermoplastic polymer is selected from PTT or PBT.

[0049] In another particular embodiment, the first thermoplastic polymer is selected from polyamide, preferably PA6 or PA6,6. The first plastic material may further comprise one or more additives. Generally speaking, additives are used to enhance certain properties in the area of ​​plastic products made with the first plastic material. For example, the additives may be selected from the group consisting of, but not limited to, plasticizers, colorants, processing aids, rheological agents, antistatic agents, anti-UV agents, reinforcement agents, anti-fog agents, compatibilizers, slip agents, flame retardants, antioxidants, light stabilizers, oxygen scavengers, inks, adhesives, fertilizers and phytosanitary products. Advantageously, the first plastic material comprises less than 30% by weight (wt%), preferably less than 15 wt%, more preferably less than 5 wt% or less than 1 wt% of such additives.

[0050] In one particular embodiment, a compatibilizer can be added to the first plastic material to enhance adhesion between the first plastic material and the second plastic material. For example, a compatibilizer for polyester can be selected from polyacrylates, ethylene terpolymers, acrylic acid esters, glycidyl methacrylate, triblock copolymers, maleic anhydride and / or maleic anhydride grafted polymers.

[0051] In one particular embodiment, the first plastic material comprises an acid-resistant filler. The term "acid-resistant filler" is used to refer to a filler that has the ability to chemically neutralize acid molecules even contained in the plastic material (or generated by the decomposition of such a plastic material). The neutralization reaction carried out by the acid-resistant filler is generally based on ion exchange. The presence of the acid-resistant filler in the plastic material may help to increase and / or maintain the pH of the composition. The acid-resistant filler may be inorganic or organic, synthetic or natural, and may be used alone or as a mixture of several acid-resistant fillers. The acid-resistant filler may be selected from hydrotalcite, calcium carbonate, talc, mica, clay and / or calcium hydroxide. Preferably, the acid-resistant filler represents a weight percentage between 0.1% and 30%, preferably between 2wt% and 15wt%, more preferably between 1wt% and 10wt% of the first plastic material, based on the total weight of the plastic material.

[0052] Advantageously, the first thermoplastic material comprises less than 30 wt%, preferably less than 15 wt%, more preferably less than 5 wt% or less than 1 wt% of both additives and acid-resistant fillers.

[0053] Second Thermoplastic Material According to the invention, the second plastic material comprises a second thermoplastic polymer, a degrading enzyme and, optionally, additives and / or fillers. Preferably, the second plastic material comprises at least 70%, 75%, 80%, 85%, 90%, 95% by weight of the second thermoplastic polymer, based on the total weight of the thermoplastic material. The additives and / or fillers, including compatibilizers, may be the same or different from the additives and fillers of the first plastic material. Advantageously, the second plastic material comprises less than 30% by weight, preferably less than 15 wt%, more preferably less than 5 wt% or even less than 1 wt% of such additives and / or fillers, based on the total weight of the thermoplastic material. In a particular embodiment, said second thermoplastic polymer is a mixture of different grades of polymers of the same type (i.e. having the same chemical formula).

[0054] Advantageously, the second thermoplastic material has a transformation temperature (Tf) of less than 180° C., preferably less than 150° C., more preferably less than 120° C., even more preferably less than 100° C. In particular, the second thermoplastic material comprises at least 70%, 75%, 80%, 85%, 90%, preferably at least 95% by weight of a second semi-crystalline thermoplastic polymer, based on the total weight of the second thermoplastic material, said semi-crystalline thermoplastic polymer having a melting temperature (Tm) of less than 180° C., preferably less than 150° C., more preferably less than 120° C. According to the invention, the second plastic material comprises at least one thermoplastic polymer different from the thermoplastic polymer of the first plastic material (e.g. having a different chemical formula, having a different grade and / or of a different formulation so as to reach a different viscosity).

[0055] Preferably, the second thermoplastic polymer is selected from water insoluble polymers.

[0056] Advantageously, the second thermoplastic polymer is selected from thermoplastic polymers having a transformation temperature (Tf) of less than 180°C and / or a glass transition temperature (Tg) of less than 70°C. Preferably, the second thermoplastic polymer is selected from thermoplastic polymers having a Tf of less than 150°C and / or a Tg of less than 30°C. More preferably, the second thermoplastic polymer is selected from thermoplastic polymers having a Tf of less than 120°C. In another particular embodiment, the second thermoplastic polymer is selected from semi-crystalline polymers having a melting temperature (Tm) of less than 180°C, preferably less than 150°C, more preferably less than 120°C, even more preferably a Tm of less than 100°C and / or a Tg of less than 70°C, preferably less than 30°C. In another embodiment, the second thermoplastic material comprises a mixture of a semi-crystalline second thermoplastic polymer and an amorphous second thermoplastic polymer, the mixture of polymers having a Tf of less than 180°C, preferably less than 150°C, more preferably less than 120°C and / or a Tg of less than 70°C, preferably less than 30°C. In another embodiment, the second thermoplastic polymer is selected from amorphous polymers having a softening temperature of less than 180°C, preferably less than 150°C, more preferably less than 120°C and / or a Tg of less than 70°C, preferably less than 30°C.

[0057] In one particular embodiment, the second thermoplastic polymer is selected from polylactic acid (PLA), polycaprolactone (PCL), polybutylene adipate terephthalate (PBAT), polyhydroxyalkanoate (PHA), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate (PBA), polyglycolic acid (PGA), ethylene-vinyl acetate (EVA), polydioxanone (PDS), polyethylene glycol (PEG), preferably PEG with a molecular weight of more than 600 g / mol, polyethylene oxide (PEO), copolymers and / or derivatives thereof. In one particular embodiment, the second polymer is a copolymer of polylactic acid and polyglycolic acid (PLGA or PLA-co-PGA). In another particular embodiment, the second polymer is PCL. In another particular embodiment, the second polymer is PLA.

[0058] The second plastic material preferably contains at least 0.001 wt% of pure degradative enzymes, based on the total weight of the second plastic material. In a particular embodiment, the second plastic material comprises 0.001-30 wt%, preferably 0.1%-20 wt%, more preferably between 0.1% and 10 wt% of pure degradative enzymes. In a particular embodiment, the second plastic material comprises about 1 wt% of pure degradative enzymes. In the context of the present invention, "pure" degradative enzymes refers to enzymes without any excipients, additives, etc. In a particular embodiment, the second thermoplastic material comprises (i) 70-99.9 wt% of at least one polyester, preferably at least one polyester selected from PCL, PBAT, PBSA, PBS, PBA, PGA, PLA, PLGA and PHA, and (ii) 0.1-10 wt% of pure degradative enzymes, based on the total weight of the second thermoplastic material.

[0059] According to the present invention, the degradative enzyme is selected from among the enzymes capable of degrading the first thermoplastic polymer. Examples of suitable degradative enzymes include, but are not limited to, depolymerases, hydrolases, esterases, lipases, cutinases, proteases, polyesterases, carboxylesterases, oxygenases and / or oxidases, such as laccases, peroxidases or oxygenases. The enzymes may be in pure or concentrated form, such as concentrated supernatants, or may be mixed with other excipients or diluents. Combinations of enzymes may be used as well. A person skilled in the art will be able to select the appropriate degradative enzyme depending on the nature of the thermoplastic polymer of the first plastic material that must be degraded.

[0060] For example, when the first thermoplastic polymer is PLA, the degradative enzyme may be a protease, preferably a proteinase K from the genus Amycolatopsis, Amycolatopsis orientalis, Tritirachium album, Actinomadura keratinilytica, Laceyella sacchari LP175, Thermus, Bacillus licheniformis, Bacillus thermoproteolyticus, Bacillus The protease may be selected from any commercially available enzyme known to degrade PLA, such as Savinase®, Esperase®, Alcalase®, Everlase®, Protex®, Optimase®, Multifect®, or any enzyme from the family of subtilisin CAS 9014-01-1 or any functional variant thereof. Examples of suitable proteases are described in WO 2016 / 062695, WO 2016 / 146540 or WO 2018 / 109183. If necessary, the commercially available enzyme may be modified (e.g. diafiltered to remove the commercially available carrier) before being mixed with the second thermoplastic polymer. Examples of such modifications are described in WO 2019 / 043145.

[0061] When the first thermoplastic polymer is PET, the degradative enzyme may be cutinase, preferably selected from the group consisting of Thermobifida cellulosityca, Thermobifida halotolerans, Thermobifida fusca, Thermobifida alba, Bacillus subtilis, Fusarium solani pisi, Humicola insolens, Sirococcus conigenus, Ideonella sakaiensis, Pseudomonas mendocina and Thielavia terrestris. The cutinase may be selected from a cutinase selected from Humicola insolens, such as that referenced in UniProt at A0A075B5G4, or any functional variant thereof. In another embodiment, the cutinase is selected from a metagenomic library, such as the LC cutinase described in Sulaiman et al., 2012, or any functional variant thereof. Examples of suitable cutinases are described in WO 2018 / 011284 and WO 2018 / 011281. In another particular embodiment, the depolymerase is a cutinase from Humicola insolens, such as that referenced in UniProt at A0A075B5G4, or any functional variant thereof. In another embodiment, the depolymerase is a commercially available enzyme, such as Novozym 51032, or any functional variant thereof.

[0062] In one particular embodiment, the degradative enzyme is capable of further degrading a polymer of a second thermoplastic material. In a particular example, a cutinase selected to degrade PET of the first thermoplastic material is also capable of degrading PCL of the second thermoplastic material.

[0063] In another embodiment, the second thermoplastic material comprises a degradative enzyme selected from enzymes capable of degrading the first thermoplastic polymer and an additional degradative enzyme selected from enzymes capable of degrading the second thermoplastic polymer. For example, the second thermoplastic material comprises PCL, an enzyme capable of degrading PCL (e.g., a lipase), and a protease capable of degrading the PLA of the first thermoplastic material.

[0064] In another embodiment, a compatibilizer can be added to the second plastic material to enhance adhesion with the second plastic material. For example, a compatibilizer for polyester can be selected from polyacrylates, ethylene terpolymers, acrylic acid esters, glycidyl methacrylate, triblock copolymers, maleic anhydride and / or maleic anhydride grafted polymers.

[0065] In a particular embodiment, the second plastic material comprises an acid-resistant filler, which is advantageous because the depolymerase activity of the decomposition enzyme in the plastic material in the presence of the acid-resistant filler is greater than in the absence of the acid-resistant filler. Preferably, the acid-resistant filler represents a weight percentage of 0.1% to 30%, preferably 2wt% to 15wt%, of the second plastic material, based on the total weight of the plastic material.

[0066] In one particular embodiment, the second plastic material comprises, based on the total weight of the second plastic material: (i) 70-99.8 wt. % of at least one polyester, preferably PCL, PBAT, PBSA, PBS, PBA, PGA, PLA, PLGA or PHA, (ii) 0.1 to 29.9 wt. % of at least one acid-resistant filler and / or additive comprising a compatibilizer, preferably an additive comprising a compatibilizer selected from hydrotalcite, calcium carbonate, talc, mica, clay and / or calcium hydroxide; (iii) 0.1-10 wt% pure decomposition enzyme Includes.

[0067] In one particular embodiment, the degradative enzymes are in liquid form, i.e. in a formulation containing the enzyme(s) and diluent(s) and / or carrier(s), such as stabilizing component(s) and / or solubilizing component(s), such as water, glycerol, sorbitol, dextrins, (e.g. maltodextrin and / or cyclodextrin), starch, gum arabic, glycols (e.g. propanediol and monoethylene glycol), salts, etc., and the second thermoplastic polymer is selected from semi-crystalline polymers having a Tm below 120° C., preferably below 100° C., more preferably below 80° C. Preferably, the degradative enzymes are in liquid form, formulated with water and / or monoethylene glycol and / or sorbitol, more preferably with water.

[0068] In one particular embodiment, the second plastic material comprises, based on the total weight of the second plastic material: (i) 70-99.8 wt. % of at least one semi-crystalline polyester having a Tm of less than 120° C., preferably less than 100° C., more preferably less than 80° C., preferably selected from PCL, PBAT, PBSA, PBS, PBA, PGA, PLA, PLGA or PHA; (ii) 0.1 to 29.9 wt % of at least one diluent and / or carrier; (iii) 0.1-10 wt% pure decomposition enzyme Includes.

[0069] In a particular embodiment, the second plastic material further comprises other heat-sensitive components, such as, but not limited to, plant protection agents, repair enzymes, luminescent enzymes, insect repellents, fragrances, or drugs, in particular, said heat-sensitive compounds remain active in the final multi-component plastic product.

[0070] Multi-component plastic products The object of the present invention is to provide a new multi-component plastic product comprising two or more thermoplastic materials composed of different thermoplastic polymers, in which one of the thermoplastic materials comprises a degrading enzyme suitable for degrading a polymer of another thermoplastic material of the multi-component plastic product. According to the present invention, the degrading enzyme is capable of degrading a first thermoplastic polymer in the multi-component plastic product, i.e. the degrading enzyme still shows a degrading activity even after (one or more) heat treatments to produce the multi-component plastic product.

[0071] According to the invention, a multi-component product comprises at least two different thermoplastic materials, a first thermoplastic material comprising a first thermoplastic polymer and a second thermoplastic material comprising at least one second thermoplastic polymer and at least one degrading enzyme capable of degrading the first thermoplastic polymer, the second thermoplastic material having a transformation temperature (Tf) strictly lower than the transformation temperature (Tf) of the first thermoplastic material, and the first thermoplastic material and the second thermoplastic material being at least partially adjacent in the multi-component product.

[0072] In a preferred embodiment, the second thermoplastic material has a transformation temperature that is at least 50° C. lower, preferably 60° C., 70° C., 80° C. lower than the transformation temperature of the first thermoplastic material.

[0073] In one particular embodiment, the first plastic material comprises at least 70%, 75%, 80%, 85%, 90%, 95%, 99% by weight of a first thermoplastic polymer, based on the total weight of the first plastic material, the first thermoplastic polymer being selected from semi-crystalline polymers having a Tm above 120° C., preferably above 150° C., more preferably above 180° C., and the second plastic material comprises at least 70%, 75%, 80%, 85%, 90%, 95%, 99% by weight of a second thermoplastic polymer, based on the total weight of the second plastic material, the second thermoplastic polymer being selected from semi-crystalline polymers having a Tm below 180° C., preferably below 150° C., more preferably below 120° C., even more preferably below 100° C. In particular, the first polymer has a Tm above 180° C. and the second polymer has a Tm below 120° C. Alternatively, the first polymer has a Tm greater than 150°C and the second polymer has a Tm less than 100°C.

[0074] According to the invention, at least two thermoplastic materials are arranged in different parts or regions in a multi-component plastic product that are physically separate from each other, i.e., the parts or regions are not intimately mixed. In the context of the present invention, a region refers to a part of said plastic product that contains a given thermoplastic polymer, which may be different from the thermoplastic polymer of at least one adjacent region of said plastic product. The physical contact between two adjacent regions allows the degrading enzymes present in one region to degrade the thermoplastic polymer in the adjacent region and eventually spread to this region.

[0075] In one particular embodiment, the plastic product is a bicomponent plastic product made of two distinct thermoplastic materials, as described above. The two distinct thermoplastic materials may be arranged in two or more distinct parts. According to the invention, at least two parts made of distinct plastic materials are adjacent. The thermal treatment or transformation process or processing step used to manufacture the multicomponent product is advantageously coextrusion, coinjection or extrusion coating, preferably coextrusion. The multicomponent product is advantageously selected from multicomponent filaments and multilayer plastic products.

[0076] In one embodiment, the multicomponent product is a multicomponent filament. Advantageously, the heat treatment or transformation process used to manufacture the multicomponent filament is coextrusion.

[0077] In particular, the multicomponent filament comprises at least two different thermoplastic materials, the first thermoplastic material comprises at least 70%, 75%, 80%, 85%, 90%, preferably at least 95% by weight of a first semi-crystalline thermoplastic polymer based on the total weight of the first thermoplastic material; the second thermoplastic material comprises at least 70%, 75%, 80%, 85%, 90%, preferably at least 95% by weight of a second semi-crystalline thermoplastic polymer based on the total weight of the second thermoplastic material, and at least one degrading enzyme capable of degrading said first semi-crystalline thermoplastic polymer; The second semi-crystalline thermoplastic polymer has a melting temperature (Tm) lower than the melting temperature (Tm) of the first semi-crystalline thermoplastic polymer, preferably at least 50°C lower, more preferably 60°C, 70°C, 80°C lower.

[0078] Advantageously, the first thermoplastic polymer is selected from semi-crystalline polymers having a Tm above 120° C., preferably above 150° C., more preferably above 180° C., and the second thermoplastic polymer is selected from semi-crystalline polymers having a Tm below 180° C., preferably below 150° C., more preferably below 120° C., even more preferably below 100° C. In particular, the first polymer has a Tm above 180° C. and the second polymer has a Tm below 120° C. Alternatively, the first polymer has a Tm above 150° C. and the second polymer has a Tm below 100° C.

[0079] For example, the multicomponent product is a bicomponent filament composed of a first thermoplastic material and a second thermoplastic material, and the resulting cross section of the bicomponent filament can resemble a variety of different configurations. For example, the first and second regions of the bicomponent filament can be arranged in a sheath / core, tipped trilobal, bicomponent trilobal, side-by-side, islands-in-the-sea, or segmented pie configuration. Further arrangements may be in a circular cross-sectional shape, an elliptical cross-sectional shape, a star shape, a flat shape, or a rectangular shape. In one particular embodiment, the first and second thermoplastic materials are arranged in a sheath / core configuration. In another particular embodiment, the thermoplastic materials are arranged in a segmented pie or islands-in-the-sea configuration to improve enzyme accessibility to the first polymer. Such islands-in-the-sea configuration provides degradability to the plastic product, but the enzymes do not come into contact with the outside of the product. This type of multicomponent product can be of particular interest for the production of products and / or foods intended to come into contact with the skin of a subject. In one particular embodiment, the multicomponent product is a bicomponent filament comprising a sheath made of a first plastic material and a core made of a second plastic material. This type of filament can be particularly interesting for the manufacture of products that can come into contact with the skin and / or food of a subject. Indeed, the enzyme is contained in the core of the filament, so that direct contact with the skin or food during storage and use is limited.

[0080] Alternatively, the bicomponent filament includes a core made of a first plastic material and a sheath made of a second plastic material.

[0081] In one particular embodiment, the multicomponent product is a multicomponent filament having a diameter of less than 5 mm, preferably less than 2 mm. Such multicomponent filaments can be used for subsequent production of plastic products using 3D printing or any means suitable for molding plastic products. Examples of cross sections of such multicomponent filaments include, but are not limited to, sheath / core, side-by-side, islands-in-the-sea, or segmented pie cross sections.

[0082] In another embodiment, the multicomponent product is a multicomponent filament with a diameter of less than 250 μm, preferably less than 50 μm. Such type of filament advantageously exhibits a circular (sheath / core, side-by-side, islands-in-the-sea, or segmented pie) or trilobal cross section. Such multicomponent filaments can be used to produce yarns for producing textile products. The yarns are produced by extruding several tens of filaments together using a melt-spinning extruder, resulting in the production of multifilament yarns, each filament being multicomponent. In a particular embodiment, the yarns can be used in clothing, nonwoven products, and netting. Nonwoven products may also be produced directly by spunlaid (spunbond or meltblown) of the filaments. In a particular embodiment, the multicomponent product is a multicomponent filament comprising at least two thermoplastic materials, the first material comprising PLA and the second thermoplastic material having a transformation temperature at least 50° C. lower, preferably 60° C., 70° C., 80° C. lower than the transformation temperature of the first thermoplastic material. In particular, the second thermoplastic material comprises PCL.

[0083] In one particular embodiment, the multicomponent product is a multicomponent filament comprising at least two thermoplastic materials, the second thermoplastic material comprising PCL and a PLA degrading enzyme and the first thermoplastic material comprising PLA, preferably said multicomponent filament is produced by coextrusion.

[0084] In one particular embodiment, the multi-component product is a multi-component filament, the second thermoplastic material comprises PLA and a PLA degrading enzyme, the first thermoplastic material comprises PLA, the first thermoplastic material comprises a grade of PLA having a higher Tf and / or Tm than the grade of PLA of the second thermoplastic material, and / or the second plastic material further comprises additional component(s) such as a plasticizer, a filler, or a polymer(s) to reduce the viscosity of the second plastic material.

[0085] In one particular embodiment, the multicomponent product is a multicomponent filament comprising at least two thermoplastic materials, a first material comprising PET or a copolymer of PET such as PET-G, and a second thermoplastic material having a transformation temperature at least 50° C. lower than the transformation temperature of the first thermoplastic material, preferably 60° C., 70° C., 80° C. lower. In particular, the second thermoplastic material comprises PCL, PBAT, PBSA, PBS, PBA, PGA, PLA, PLGA or PHA. In particular, the multicomponent product is a multicomponent filament, the second thermoplastic material comprises PCL, PBAT, PBSA, PBS, PBA, PGA, PLA, PLGA or PHA and a PET degrading enzyme, the first thermoplastic material comprises PET or a copolymer thereof such as PET-G, and the first thermoplastic material PET has a higher Tf and / or Tm than the second thermoplastic material PCL, PBAT, PBSA, PBS, PBA, PGA, PLA, PLGA or PHA, preferably at least 50° C. higher, more preferably at least 60° C., 70° C., 80° C., 150° C. higher. Preferably, said multicomponent filament is produced by coextrusion.

[0086] In another embodiment, the multi-component product is selected from multi-layer plastic products, including multi-layer plastic films, multi-layer plastic sheets, multi-nano-layer plastics, multi-layer plastic trays, multi-layer plastic bottles, multi-layer packaging, multi-layer profiles and tubes. The heat treatment or transformation process used to manufacture the multi-component product is advantageously co-extrusion, co-injection or extrusion coating. In particular, the heat treatment or transformation process used to manufacture the multi-layer plastic trays, multi-layer plastic bottles or multi-layer packaging is co-injection.

[0087] In one particular embodiment, the multi-component product is a multi-layer plastic product, where at least one layer made of a second plastic material is adjacent to at least one layer made of a first plastic material. The multi-component product may contain additional layers or regions of any kind (plastic materials, metal compounds such as aluminum or foil, glass or carbon fibers, etc.). The layers may have different lengths and / or thicknesses. The layers may overlap completely or partially. The layers may be bonded with specific adhesives during manufacturing through a dedicated process or may naturally adhere to each other due to polymer compatibility.

[0088] In another particular embodiment, a multi-layer plastic product includes at least one layer made of a second plastic material sandwiched between two layers made of a first plastic material.

[0089] Advantageously, the weight ratio of the first plastic material / second plastic material of the multicomponent product is comprised between 50 / 50 and 99 / 1, between 60 / 40 and 98 / 2 or between 70 / 30 and 95 / 5. In one particular embodiment, the multicomponent product is a bicomponent filament comprising a core of a first plastic material and a sheath of a second plastic material, the core representing 30-40% by weight of the total weight of the bicomponent filament and the sheath representing 60-70% by weight of the total weight of the bicomponent filament. In another particular embodiment, the multicomponent product is a bicomponent filament comprising a core of a first plastic material and a sheath of a second plastic material, the core representing 5-25% by weight of the total weight of the bicomponent filament and the sheath representing 75-95% by weight of the total weight of the bicomponent filament.

[0090] In one particular embodiment, the multicomponent product is a multi-layer plastic product, in which at least one layer of the second plastic material represents 1 to 50% by weight, preferably 1 to 20% by weight, of the total weight of the multi-layer plastic product, and at least one layer of the first plastic material represents 50 to 99% by weight, preferably 80 to 99% by weight, of the total weight of the bicomponent filaments.

[0091] In one particular embodiment, the multi-component product is a multi-layer plastic product, in which at least one layer of a second plastic material sandwiched between two layers of a first plastic material represents a weight percentage between 1% and 50%, preferably between 1% and 20%, of the total weight of the multi-layer plastic product, and the two layers of the first plastic material represent a weight percentage between 50% and 99%, preferably between 80% and 99%, of the total weight of the bi-component filaments.

[0092] In one particular embodiment, the multi-component product comprises at least two thermoplastic materials, a first thermoplastic polymer is PLA and a second thermoplastic polymer is PCL.

[0093] In another particular embodiment, the multi-component product comprises at least two thermoplastic materials, a first thermoplastic polymer is PET or a copolymer of PET such as PET-G, and a second thermoplastic polymer is selected from PCL, PBAT, PBSA, PBS, PBA, PGA, PLA, PLGA, or PHA.

[0094] In another particular embodiment, the multi-component product comprises at least two thermoplastic materials, a first thermoplastic polymer is PBT or PTT and a second thermoplastic polymer is selected from PCL, PBAT, PBSA, PBS, PBA, PGA, PLA, PLGA or PHA.

[0095] In one particular embodiment, the multi-component product is a multi-layer plastic product, where at least one layer made of a second plastic material comprises PCL and a PLA degrading enzyme and at least one layer made of a first plastic material comprises at least PLA, In one particular embodiment, at least one layer made of a second plastic material comprising PCL and a PLA degrading enzyme is sandwiched between two layers made of a first plastic material comprising PLA.

[0096] In another particular embodiment, the multi-component product is a multi-layer plastic product, at least one layer made of a second plastic material comprising at least one polyester selected from PCL, PBAT, PBSA, PBS, PBA, PGA, PLGA, PLA or PHA and a PET degrading enzyme, said layer being sandwiched between two layers made of a first plastic material comprising PET or a copolymer of PET such as PET-G.

[0097] In another particular embodiment, the multi-component product is a multi-layer plastic product, where at least one layer made of PCL and a second plastic material comprising a PET degrading enzyme is sandwiched between two layers made of a first plastic material comprising at least PET.

[0098] Manufacturing method The object of the present invention is to provide a method for the preparation of a multi-component plastic product having one or more first regions made of a first plastic material, which first regions are at least partially adjacent to one or more second regions made of a second plastic material.

[0099] According to the invention, a method for producing a multi-component product comprises the steps of: a. selecting a first plastic material comprising a first thermoplastic polymer; b. selecting a degrading enzyme capable of degrading a first thermoplastic polymer; c. mixing the degradative enzyme with a second thermoplastic polymer at a temperature at which the second thermoplastic polymer is partially or completely molten to obtain a second plastic material, the second thermoplastic material having a transformation temperature (Tf) strictly lower than the transformation temperature (Tf) of the first thermoplastic material; d. co-extruding or co-injecting or extrusion coating said plastic material to obtain a multi-component product.

[0100] Preferably, the second thermoplastic material has a transformation temperature that is at least 50°C lower, preferably 60°C, 70°C, 80°C lower than the transformation temperature of the first thermoplastic material.

[0101] In one particular embodiment, the first thermoplastic material comprises at least 70%, 75%, 80%, 85%, 90%, preferably at least 95% by weight of a first semi-crystalline thermoplastic polymer, based on the total weight of the first thermoplastic material, and the second thermoplastic material comprises at least 70%, 75%, 80%, 85%, 90%, preferably at least 95% by weight of a second semi-crystalline thermoplastic polymer, based on the total weight of the second thermoplastic material, and the second semi-crystalline thermoplastic polymer has a melting temperature lower than the melting temperature of the first semi-crystalline thermoplastic polymer.

[0102] The degradative enzyme is mixed with the second thermoplastic polymer and optional additives or fillers at a temperature at which the second thermoplastic polymer is partially or completely molten. Methods for introducing degradative enzymes into plastic materials are described, for example, in WO 2013 / 093355, WO 2016 / 198652, WO 2016 / 198650, WO 2016 / 146540, WO 2016 / 062695 and WO 2019 / 043145. According to the present invention, after both the first heat treatment for preparing the second thermoplastic material and the second heat treatment for forming the multi-component plastic product, the degradative enzyme still exhibits degradative activity.

[0103] The degradative enzyme is advantageously mixed with the second thermoplastic polymer in an amount of 0.001 to 30% by weight (pure enzyme), preferably 0.1% to 20% by weight of pure degradative enzyme, more preferably 0.1% to 10% by weight, based on the total weight of the second plastic material. In a particular embodiment, the second plastic material is prepared by introducing the degradative enzyme into the second thermoplastic polymer during heating of the latter. More generally, the preparation step of the second plastic material is carried out at a temperature at which the second polymer is partially or completely in a molten state, so that the enzyme is incorporated in the second polymer. Preferably, such preparation is carried out by extrusion. Alternatively, such preparation is carried out by internal mixing or co-mixing. In a particular embodiment, the degradative enzyme in liquid form is mixed with the second thermoplastic polymer. Preferably, the degradative enzyme is a formulation containing the enzyme(s) and water, the second thermoplastic polymer being selected from semi-crystalline polymers having a Tm below 120°C, preferably below 100°C, more preferably below 80°C.

[0104] In a preferred embodiment, the second plastic material is prepared by introducing the second thermoplastic polymer and the degrading enzyme into an extruder, such as a twin screw extruder. The resulting extrudate can be granulated into solid pellets and optionally dried until the residual moisture is reduced to less than 5%, preferably less than 2%, more preferably less than 1%, even more preferably less than 0.5%.

[0105] Such pellets, or more generally a second plastic material, can then be used to prepare a multi-component product.

[0106] According to the invention, the multi-component plastic product is obtained by shaping a first plastic material and a second plastic material during a thermal treatment, advantageously both the first plastic material and the second plastic material being in a partially and / or completely molten state.

[0107] In a particular embodiment, the thermal process is a co-extrusion process, in which the two plastic materials are introduced into separate extruders, melted and joined in a common die. Each extruder is advantageously equipped with one or more heating zones, allowing the temperature to be controlled independently. It is thus possible to adapt the temperature in each extruder to the thermoplastic polymer of the plastic material considered. Each plastic material is thus in a partially or completely molten state when it arrives in the common die.

[0108] In one particular embodiment, the temperature in the common die corresponds to the highest temperature between the two extruders, so that both plastic materials are maintained in a partially and / or completely molten state. Thus, the second plastic material containing the degrading enzyme is exposed to the highest temperature only during the final step of molding. In another particular embodiment, the temperature in the common die may be a temperature between the lowest and highest temperatures of both extruders, provided that both plastic materials are maintained in a partially and / or completely molten state in the die.

[0109] The object of the present invention is also to a. selecting a first plastic material comprising a first thermoplastic polymer; b. selecting a degrading enzyme capable of degrading a first thermoplastic polymer; c. mixing the degradative enzyme with a second thermoplastic polymer at a temperature at which the second thermoplastic polymer is partially or completely molten to obtain a second plastic material; d. processing said thermoplastic material at a temperature in which said thermoplastic material is partially or completely molten to provide a method for producing a multi-component product, the processing temperature of the second plastic material being lower, preferably at least 50° C. lower, than the processing temperature of the first thermoplastic material; The present invention also provides a method for producing a multi-component product comprising:

[0110] Advantageously, the processing step used to manufacture the multicomponent product is coextrusion, coinjection or extrusion coating, preferably coextrusion.

[0111] In one particular embodiment, the first thermoplastic polymer is PLA and the second thermoplastic polymer is PCL, the processing temperature (or extrusion temperature, i.e. the temperature in the extruder) of PLA is 120°C to 180°C, + / - 10°C, whereas the processing temperature (or extrusion temperature, i.e. the temperature in the extruder) of PCL is 60°C to 110°C, + / - 5°C, with a common die temperature of 180°C, + / - 10°C.

[0112] In another particular embodiment, the first thermoplastic polymer is PLA and the second thermoplastic polymer is PCL, the processing temperature (or extrusion temperature, i.e. the temperature in the extruder) of PLA is 190°C to 230°C, + / - 10°C, whereas the processing temperature (or extrusion temperature, i.e. the temperature in the extruder) of PCL is 70°C to 120°C, + / - 5°C, and the temperature in the common die is 190°C, + / - 10°C.

[0113] In one particular embodiment, the first thermoplastic polymer is PETG and the second thermoplastic polymer is PCL, the processing temperature (or extrusion temperature, i.e. the temperature in the extruder) of PETG is 190°C to 230°C, + / - 10°C, whereas the processing temperature (or extrusion temperature, i.e. the temperature in the extruder) of PCL is 60°C to 120°C, + / - 5°C, with a common die temperature of 180°C, + / - 10°C.

[0114] In one particular embodiment, the first thermoplastic polymer is PET and the second thermoplastic polymer is PCL, the processing temperature (or extrusion temperature, i.e. the temperature in the extruder) of PET is 250°C to 280°C, + / - 10°C, whereas the processing temperature (or extrusion temperature, i.e. the temperature in the extruder) of PCL is 60°C to 150°C, + / - 5°C, with a common die temperature of 240°C, + / - 10°C.

[0115] More generally, the first plastic material and the second plastic material preferably have similar viscosities when they reach the common die. In the context of the present invention, the viscosity of a thermoplastic polymer and the viscosity of a plastic material containing said thermoplastic polymer are quantities that describe the flow resistance of a fluid. Formally, viscosity is the ratio of the shear stress to the velocity gradient in a fluid.

[0116] In a particular embodiment, the shaping step of the plastic product is carried out by a common die or extruder spinning pack in a coextrusion process. A person skilled in the art will adapt the die or the coextruder spinning pack to the required shape. The extruder can include a coextrusion die selected from a sheet die, a flat film die, a circular film die, a pipe or tube die, a profile extrusion die. For example, a vertical die with small diameter holes produces bicomponent filament or multicomponent multifilament fabrics, i.e. textile products consisting of several bicomponent or multicomponent filaments. A horizontal die with one or more holes produces multicomponent fabric filaments or 3D printing filaments. A flat die with elongated slots produces multilayer films or sheets for thermoforming applications. An annular die in blow molding extrusion produces multilayer films. Other dies with specific shapes produce tubes or multilayer profiles. The multilayer extrusion blow molding process can lead to the production of multilayer cans and bottles, injecting air into the tube exiting the die.

[0117] In one particular embodiment, the co-extruder is equipped with a spinning bundle or die having a multifilament spinneret or a monofilament spinneret to produce bicomponent or multicomponent 3D printed monofilament, bicomponent or multicomponent monofilament fabric, or bicomponent or multicomponent multifilament fabric, spunbond or meltblown nonwoven.

[0118] In another particular embodiment, the thermal treatment is an extrusion coating process in which an extruder forces one plastic material through a horizontal die onto a moving solid sheet or film composed of another plastic material.

[0119] In another particular embodiment, the heat treatment is a co-injection process, in which the two plastic materials are introduced into separate extruders, each of which is equipped with two independent injection ports at its end. Each extruder is advantageously equipped with one or more heating zones, allowing the temperature to be controlled independently. This makes it possible to adapt the temperature in each extruder to the thermoplastic polymer of the plastic material considered. This allows each plastic material to be in a partially or completely molten state when it reaches its respective injection port. The first plastic material, which contains the polymer to be decomposed, and the second plastic material can be injected into the mold simultaneously or sequentially.

[0120] The resulting multi-component plastic product is advantageously an aerobic and / or anaerobic biodegradable plastic product according to at least one of the relevant standards and / or labels known to the skilled person, such as, for example, standard EN13432, standard NFT51800, standard ASTM D6400, OK Biodegradation Soil (Label TUEV Austria), OK Biodegradation Water (Label TUEV Austria), OK Compost (Label TUEV Austria), OK Compost Home (Label TUEV Austria), standard ISO15985:2014, standard ASTM D5526, standard ISO15985, standard ASTM D5511. Alternatively, the resulting multi-component plastic product can be used to produce methane. Such plastic products can be used in the manufacture of composites (for example, polymer matrix and glass or carbon fibers) to improve delamination of the different parts of the composite. For example, a composite material comprises a multicomponent product of the invention and glass or carbon fibers incorporated therein. The biodegradability of the polymer matrix (i.e., the multicomponent product) allows for the recovery of the glass or carbon fiber(s) at the end of the composite's life. In another embodiment, the polymer matrix comprises a recyclable polymer and the multicomponent fibers of the invention are incorporated therein. The biodegradability of the multicomponent fibers allows for the recovery of the polymer for subsequent recycling.

[0121] Contains other heat-sensitive ingredients It is also an object of the present invention to provide a plastic product containing any heat-sensitive compound. Thus, the present invention provides a plastic product comprising two or more separate plastic materials composed of different thermoplastic polymers and at least one heat-sensitive compound. A first plastic material does not contain a heat-sensitive compound, while another plastic material contains a heat-sensitive compound. The heat-sensitive compound is incorporated within the second plastic material. According to the present invention, the two or more plastic materials are at least partially adjacent and not intimately mixed.

[0122] The present invention also provides a method for the preparation of such a multi-component plastic. Interestingly, the present invention makes it possible to introduce a heat-sensitive compound into a thermoplastic material having a transformation temperature lower than that of the thermoplastic material not containing the heat-sensitive compound. Thus, by the method of the present invention it is possible to prepare a thermoplastic product containing both a thermoplastic polymer having a high transformation temperature and a heat-sensitive compound, the heat-sensitive compound still being active in the thermoplastic product.

[0123] In particular, such heat-sensitive compounds may be selected from plant protection agents, repair enzymes (e.g. enzymes that detect and repair incorrect base insertions during DNA synthesis; enzymes that repair polymers, such as PHA synthases, esterases and / or lipases), luminescent enzymes, insect repellents, fragrances, or drugs.

[0124] In one particular embodiment, the thermosensitive compound is a drug selected from pharmaceutical compounds, peptides, proteins, antibiotics, analgesics, vaccines, vaccine adjuvants, anti-inflammatory drugs, antitumor drugs, hormones, cytokines, antifungal drugs, antiviral drugs, antibacterial drugs, antidiabetic drugs, steroids, certain enzyme inhibitors, growth promoters, immunosuppressants, immunomodulatory drugs, antihypertensive drugs, antiarrhythmic drugs, cardiac inotropic drugs, addiction treatment drugs, antiepileptic drugs, anti-aging drugs, drugs for treating neurological disorders and pain, lipid lowering drugs, anticoagulants, antibodies or antibody fragments, antigens, antidepressants or psychotropic drugs, neuromodulators; drugs for treating diseases selected from brain diseases, liver diseases, lung diseases, heart diseases, stomach diseases, intestinal diseases, ovarian diseases, testicular diseases, urinary diseases, reproductive diseases, bone diseases, muscular diseases, endometrial diseases, pancreatic diseases and / or kidney diseases, ophthalmic drugs, antiallergic drugs, contraceptives or luteinizing drugs, and mixtures of at least two of these drugs. In such embodiments, the article of manufacture of the invention is preferably a medical device selected from an implant, a film, a stent, a leaflet, a valve, a coil, a scaffolding, a bandage, a rod, a patch, a fiber, a suture, a screw, a bone plate or implant, a bone cement, and a prosthesis.

[0125] Working Example Example 1: Preparation of multi-component PLA monofilament for use in 3D printing A. Preparation of the Second Thermoplastic Material The enzyme-containing thermoplastic material (MB) was prepared by dissolving polycaprolactone polymer (PCL - Capa™ 6500 from Perstorp, T m The pellets were prepared using a 90% / 10% weight ratio of polycaprolactone and enzyme-free liquid composition (approximately 60°C, Tf 70-120°C for extrusion (cast films and sheets), 60-75°C for extrusion blow molding) and Savinase® 16L (Novozymes) blended liquid enzyme. A control composition (MBC) was prepared using the same proportions of polycaprolactone and enzyme-free liquid composition as MB.

[0126] The compositions of the enzyme formulations and the control used in MB and MBC are shown in Table 1. [Table 1]

[0127] The thermoplastic material containing the enzyme (MB) and the control material (MBC) were prepared using a co-rotating twin screw extruder (Leistritz ZSE 18MAXX). The compounder was equipped with nine consecutive heating zones Z1-Z9, whose temperature could be controlled and regulated independently. After zone Z9 there was an additional zone Z10, which corresponds to the head of the twin screw (Z10), which is also heated. In order to efficiently mix the liquids with the molten polymer, a suitable screw geometry was used. PCL and each liquid were introduced separately into the extruder. PCL was introduced into Z2 with a gravimetric dosing unit using a side feeder. The liquids were introduced directly into the first feeding zone (Z0) of the extruder using a Brabender pump. The molten polymer reached screw Z10, which contained a die plate with one hole of 3.5 mm, which was immediately immersed in a 2 m long cold water bath. The resulting extrudate was granulated into solid pellets less than 3 mm in size. In this experiment, 90 wt% PCL was extruded with 10 wt% of the liquid composition. MB and MBC were dried in a vacuum oven at 45° C. until the residual humidity dropped to less than 0.5%.

[0128] The parameters used for each extrusion composition are summarized in Table 2. [Table 2] Thermoplastic Materials

[0129] B. Preparation of multicomponent filaments by coextrusion a. Filament preparation The composition prepared in Example 1-A was used for the core (the Tf of the MB and MBC materials was determined to be 80-120°C for the filament preparation), and polylactic acid (4043D PLA grade from NatureWorks, T for biaxially oriented film defined in the technical data sheet) was used for the sheath. g 55~60℃, T mFilaments were produced using two single screw extruders (Rheoscam Scamex), one for each region joining through a die exit, with a temperature of 145-160°C, Tf of 190-200°C, Tf determined to be 170°C-200 for the filament production. The polylactic acid is known to be depolymerized by Savinase® 16L (see Oda et al., 2000 and depolymerization test in aqueous solvent (not shown)). The core extruder had four heating zones and a length / diameter (L / D) ratio of 20, which was used for the composition prepared in Example 1-A. The fourth heating zone corresponds to the bicomponent die. The sheath extruder had three heating zones and a ratio of L / D=11, which was used for PLA.

[0130] The filament temperature at the die exit was about 160°C for the 190°C die and 150-155°C for the 180°C die. The filaments were cooled with compressed air. Filaments with diameters close to 1.75 mm were obtained. In these temperature profiles, the PLA flow rate was set to its maximum and the MB / MBC flow rates were set to their minimum. The incorporation rates of the compositions prepared in Example 1-A were then measured by DSC to obtain PLA bicomponent filaments incorporating the MB composition as the core (Z2 and Z3) and a negative control filament without enzymes incorporating the MBC composition as the core (C11).

[0131] Monofilaments (M) were also made by dry blending MB from Example 1A with PLA in a 40% / 60% weight ratio, then the mixture was extruded through a die at 160° C. and into a sheath extruder at 100-170-180° C. After extrusion, the monofilaments containing such enzymes were stickier, darker in color, and had a caramel odor than the bicomponent filaments.

[0132] The process parameters are listed in Table 3 below. [Table 3]

[0133] b. Measurement of enzyme activity in the filaments A first experiment was carried out to measure the residual enzyme activity in the filaments. To recover the PCL cores containing the enzyme, the bicomponent filaments Z2 and Z3 were cut. They were then dissolved in dichloromethane and the enzyme was extracted by the addition of Tris-HCl buffer 100 mM, pH 9.5. The enzyme activity was measured with a pNA test. The test revealed that there was 45% and 56% residual activity in the cores of Z2 and Z3, respectively, compared to 100% of the enzyme activity introduced in the MB. The same experiment was performed by dissolving the filaments completely (i.e., including their PLA sheaths). The same results were obtained.

[0134] A second experiment was performed to evaluate the depolymerization of the filaments.

[0135] Depolymerization tests were carried out on cellulose dialysis tubing membranes (cut at 14 kDa) by introducing 3 mL of Mod5 (KH2PO4 0.5 g / L, K2HPO4 0.5 g / L, (NH4)2SO4 1 g / L, MgSO4-7H2O 0.2 g / L, CaCl2 0.1 g / L, ZnSO4-7H2O 0.01 g / L, FeSO4-7H2O 0.02 g / L) into 50 mL of Tris-HCl buffer 0.1 M, pH 9.5, and incubating at 45 °C or 28 °C. The released lactic acid and lactic acid dimer were measured by HPLC by taking samples in the buffer outside the dialysis tubing. The hydrolysis of the plastic products was evaluated by comparing the amount of released LA and LA dimer with the amount of LA initially contained in the PLA in the plastic composition. This test was carried out using a filament (cut into pieces of approximately 5 mm) or using a powder obtained by immersing the filament in liquid nitrogen followed by micronization at 500 μm and 18000 rpm. The filament or powder was introduced into the dialysis tubing membrane.

[0136] Table 4 below shows the depolymerization rate of the filaments at 45°C or 28°C. [Table 4]

[0137] The results show that at both temperatures (45° C. or 28° C.), the bicomponent filaments Z2 and Z3 are depolymerized faster than the dry blend filament M. Depolymerization studies performed on Z2 confirmed that enzyme activity was maintained in the bicomponent filaments even when a 190° C. die was used.

[0138] C. Test specimen fabrication by 3D printing A. Manufacturing of plastic products Using an i.FDM Printer A 3D plastic product was made from the filament of Example 1-B using an FDM printer (Neocore D33D) equipped with a 30 x 30 cm plate.

[0139] A printing temperature of 170 °C was chosen for all samples, and the bed temperature was 40 °C. The printing bed is the surface of the 3D printer where the print head places the material that constitutes the 3D print. Specimens were printed in layers of 200 μm: 75 × 12, 5 × 2 mm (three specimens using filaments C11, Z3 and M1 showing a similar appearance to one specimen of commercial PLA). The printing speed was 65-70 mm / s, which corresponds to the high speeds typically used for PLA.

[0140] ii. Using the 3D pen A sample of the Z3 filament from Example 1-B was also printed at a higher temperature (220° C.) using a 3D pen (3DPEN-2 RoHS).

[0141] b. Depolymerization test Depolymerization tests were carried out on powders obtained from 3D plastic products (produced using an FDM printer) made of C11, Z3 and M1 in dialysis tube cellulose membranes (cut at 14 kDa) by introducing 3 mL of Mod5 into 50 mL of Tris-HCl buffer 0.1 M, pH 9.5 at 45 ° C (B2401-B2406). The proportion of lactic acid and lactic acid dimer was measured by HPLC as in Example 1.Bb.

[0142] Table 5 below shows the depolymerization rate of plastic products in 1 mm powder form at 45°C. [Table 5]

[0143] The PLA depolymerization rate of the 3D plastic article of the invention (Z3) at 45° C. confirms that there is residual enzyme activity in the 3D specimens made with the filaments of the invention and that the enzyme can support three heating steps. The results show that the 3D plastic article made with the bicomponent filament Z3 depolymerizes faster than the one made with the dry blend filament M1.

[0144] PLA depolymerization tests were also performed on plastic article extrudates printed from Z3 filament with a 3D pen at 220°C compared to Z3 filament extrudates (no printing) at 45°C for 1 day. The 3D printed Z3 filament shows 39% residual enzyme activity compared to the residual enzyme activity of the initial Z3 filament (no printing). This experiment confirms that there is residual enzyme activity in 3D specimens made with the filaments of the present invention and that the enzyme can support three heating steps, even with a third heating step above 200°C.

[0145] c. Biodegradation in soil Small pieces of each plastic product made of C11 or Z3 (and produced using an FDM printer, see Example 1-Cai) were incubated in soil at 28°C in an Oxitop® respirometer and degradation was evaluated by the CO2 assay method according to standard NF U 52-001.

[0146] After 6 months, 18% biodegradation was observed in the plastic products made with the enzymatic bicomponent filament Z3, whereas only 3% biodegradation was observed in the plastic products made with the control bicomponent filament without the enzyme C11.

[0147] Co-extrusion is therefore beneficial to reduce the loss of enzyme activity due to heating during filament production and to avoid coloration associated with enzyme formulations. Bicomponent filaments can be easily 3D printed and retain enzyme activity after printing.

[0148] Example 2: Preparation of multicomponent PLA multifilament for use in textile applications A. Preparation of the Second Thermoplastic Material An enzyme loaded thermoplastic material (MB2) was prepared using pellets of polycaprolactone polymer (PCL - Capa™ 6250 from Perstorp, MFI = 7-11 g / 10 min at 80 °C) and blended enzyme Savinase® 16L (from Novozymes) in a weight ratio of 90% / 10%, respectively. The composition used is shown in Table 6. [Table 6]

[0149] Thermoplastic material MB2 was prepared in the same manner as in Example 1 and using the same co-rotating twin screw extruder (Leistritz ZSE 18MAXX).

[0150] The parameters used for the extrusion compositions are summarized in Table 7. [Table 7]

[0151] B. Preparation of multifilaments by coextrusion a. Bicomponent multifilament spinning Two PLA grades from NatureWorks were used for spinning: 6362D (amorphous PLA, Tg=66°C, MFI=70-85g / 10min at 210°C, Tf220-245°C (specialty fiber)) and 6202D (semi-crystalline PLA, Tg=66°C, Tm=168°C, initial crystallinity=36%, MFI=15-30g / 10min at 210°C, Tf220-240°C (fiber melt spinning)). 6202D is a common PLA grade used in nonwoven applications. The Tf of the 6362D and 6202D materials for the multifilament fabrication was determined to be 190°C-210°C and 220°C-240°C, respectively.

[0152] A 36-strand multifilament with MB2 in the core (for the multifilament preparation, the Tf of MB2 was determined to be 70-90°C) and PLA in the sheath was prepared using a melt-spinning extruder and winder (Hills) with three draw rolls and the parameters shown in Table 8. Both the sheath and core single screw extruders have three heating zones, a ratio of L / D=30 and a diameter of 19 mm. The die diameter is 0.35 mm. Different draw ratios were applied to the multifilaments. A control multifilament (MFC) was prepared using the same parameters shown in Table 8 and 30% PCL6250 and 70% PLA6202D. [Table 8]

[0153] b. Depolymerization test of PLA multifilament Depolymerization tests of multifilaments were carried out in dialysis tubing cellulose membranes (cut at 14 kDa) by introducing 3 mL of Mod5 into 50 mL of Tris-HCl buffer 0.1 M, pH 8, 28° C. or pH 9.5, 45° C. Lactic acid and lactate dimer were measured by HPLC according to Example 1. The results are shown in Table 9 below. [Table 9]

[0154] Depolymerization tests showed that the enzymes in the multifilament product were still active, allowing for the degradation of the PLA of the multifilament.

[0155] c. Biodegradation in soil Multifilaments MF1 and MFC were incubated in soil at 28°C in Oxytop9 and degradation was evaluated by the CO2 assay method according to standard NF U 52-001.

[0156] After 98 days, the biodegradation rate of the enzymatic bicomponent multifilament MF1 was twice that observed for the control bicomponent filament MFC, which did not contain the enzyme, at which point the biodegradation rate of the control had already reached a plateau, in contrast to the still increasing biodegradation rate of the enzymatic bicomponent multifilament.

[0157] Example 3: Preparation of multicomponent PETG filaments A. Preparation of the Second Thermoplastic Material Thermoplastic materials (MB) containing enzymes were prepared using pellets of polycaprolactone polymer (PCL-Capa™ 6500 from Perstorp) and a liquid composition containing LC cutinase in a weight ratio of 80% / 20%, respectively. LC cutinase was selected for its ability to degrade polyethylene terephthalate produced by recombinant expression in Trichoderma reesei (Sulaiman et al., Appl Environ 30 Microbiol. 2012 Mar). The ability of such cutinases to depolymerize polyethylene terephthalate glycol modified PETG (Selenis Mimesis DP 300 Natural, PET (2,2-dimethylpropane-1,3-diol) with comonomer NPG neopentyl glycol) has been verified (data not shown).

[0158] A control thermoplastic material (MBC) was prepared from the same proportions of polycaprolactone and a liquid composition without the enzyme. The liquid composition is shown in Table 10. [Table 10]

[0159] MB and MBC were prepared using the same method and the same co-rotating twin screw extruder (Leistritz ZSE 18MAXX) as in Example 1. The parameters used for each extruded composition are summarized in Table 11. [Table 11]

[0160] B. Preparation of filaments by coextrusion a. Preparation and depolymerization test of bicomponent filaments with a core made of PETG Filaments were made using the composition prepared in Example 3-A (Tf of MB and MBC was determined to be 60-70°C for the filament preparation) and PETG (Selenis Mimesis DP 300 Naturel, typical processing temperature 180-250°C). The Tf of the corresponding thermoplastic material containing PETG was 180-250°C according to the technical data sheet, which was adjusted to 190-230°C in consideration of the processing process of the filament.

[0161] The same two single screw extruders (Rheoscam Scamex) were used as in Example 1. MB or MBC formed the sheath (30%) and PETG formed the core. The die temperature was 180°C. The filaments were cooled with compressed air and a water bath. Filaments with a diameter close to 1.75 mm were obtained. The process parameters are listed in Table 12 below. [Table 12]

[0162] Depolymerization tests were performed on filaments (cut into approximately 5 mm pieces) in 50 mL of phosphate 100 mM buffer pH 8 and incubated at the optimum temperature for cutinase, 60°C, to demonstrate the enzyme activity after extrusion. Terephthalic acid release was measured by HPLC. The hydrolysis of the plastic product was evaluated by comparing the amount of terephthalic acid released with the amount of terephthalic acid initially contained in the PET in the plastic composition.

[0163] After 3 months of incubation of filaments made with MB, 52% depolymerization was obtained, indicating that enzyme activity was maintained even with a die at 180 °C. Filaments made with MBC (without enzyme) showed no depolymerization.

[0164] b. Preparation and depolymerization test of bicomponent filaments with a sheath made of PETG Filaments were made using the composition prepared in Example 3-A and PETG.

[0165] The same two single screw extruders (Rheoscam Scamex) were used as in Example 3-Ba. MB or MBC was used in the core (30%) and PETG was used in the sheath. The process parameters were the same as in Example 3-Ba (see Table 12), except for the die temperature, which was adjusted to 210°C or 230°C.

[0166] Depolymerization tests were performed similarly for filaments made with Example 3-Ba. After 3 months of incubation, filaments made with MB and 210°C and 230°C dies obtained 76% and 38% depolymerization, respectively, indicating that enzyme activity is maintained even when using a 230°C die. Filaments made with MBC (without enzyme) show no depolymerization.

[0167] Example 4: Coextrusion and depolymerization studies with a sheath made of PET A. Preparation of the Second Thermoplastic Material The enzyme-containing thermoplastic material (MB) was prepared using pellets of polycaprolactone polymer (PCL-Capa™ 6500 from Perstorp) and a liquid composition containing a mutant LC cutinase produced by recombinant expression in Trichoderma reesei (containing the following mutations F208I+D203C+S248C+V170I+Y92G) at a weight ratio of 80% / 20%, respectively.

[0168] The enzyme liquid composition is shown in Table 13. [Table 13]

[0169] The MB was prepared using a co-rotating twin screw extruder (Leistritz ZSE 18MAXX). The PCL was fed in Z2 and the liquid composition was fed in Z6. The parameters used are summarized in Table 14. [Table 14]

[0170] B. Preparation of bicomponent filaments by coextrusion The same two single screw extruders (Rheoscam Scamex) were used as in Example 3-Ba. MB was used for the core (Tf of 30%-MB material was determined to be 60-150°C for this particular filament production) and PET was used for the sheath (701K Xpure Indorama, Tm 224°C, Tf was determined to be 240-280°C for the process). The extrudate was cooled with compressed air and a water bath. The process parameters are listed in Table 15 below. [Table 15]

[0171] Depolymerization was performed at 60°C and 45°C as done in Example 3-Ba. After 13 days of incubation of filaments made with MB, 39% and 5% depolymerization was obtained at 60°C and 45°C, respectively, indicating that enzyme activity is maintained even when using a 240°C die. PET 701K without enzyme, incubated under the same conditions, shows no depolymerization. Depolymerization at 45°C is of particular interest for composting PET products.

[0172] Example 5: Preparation of a multi-component nonwoven PLA product Enzymatic MB was prepared using the enzyme blend of 90% PCL CAPA6500 and 10% Savinase 16L under the same conditions as in Example 2. 1509 filaments with a diameter of 350 μm were processed using a 37 islands-in-sea die, consisting of 20% MB in the "islands" and 80% PLA 6100D in the "sea" (Tf 220-240°C (fiber melt spinning)). The Tf of the MB and PLA materials was determined to be 70-100°C and 220-240°C, respectively, for the specific nonwoven fabric fabrication process. Two spunbond nonwoven fabrics were made with different surface masses (Hills machine). The spinning distance was 830 mm. Cooling was performed with 1.5 bar air. The laying distance was 600 mm. The nonwoven fabric was passed through a compression roll before being polished at 80°C.

[0173] The initial temperature profile was defined according to Table 16 below. [Table 16]

[0174] The nonwovens were characterized for traction and the results are summarized in Table 17 below. [Table 17]

[0175] For wiping applications, a surface mass close to 50g / 100cm2 is targeted with a tensile strength in both directions of over 25N / 50mm. For mulching applications, a higher surface mass is targeted with a tensile strength in both directions of over 50N / 50mm. The results show that enzyme-modified nonwovens can be made with different surface masses suitable for different applications with interesting properties.

Claims

1. A multi-component plastic product comprising at least two different thermoplastic materials, the first thermoplastic material comprises at least 70% by weight of a first semi-crystalline thermoplastic polymer based on the total weight of said first thermoplastic material; the second thermoplastic material comprises at least 70% by weight of a second semi-crystalline thermoplastic polymer, based on the total weight of the second thermoplastic material, and at least one degrading enzyme capable of degrading the first semi-crystalline thermoplastic polymer; A multi-component plastic product, wherein the second semi-crystalline thermoplastic polymer has a melting temperature (Tm) lower than the melting temperature (Tm) of the first semi-crystalline thermoplastic polymer, and the first thermoplastic material and the second thermoplastic material are at least partially adjacent in the multi-component plastic product.

2. 2. The multi-component plastic product of claim 1, wherein the second semi-crystalline thermoplastic polymer has a melting temperature (Tm) that is at least 50°C lower than the melting temperature (Tm) of the first semi-crystalline thermoplastic polymer.

3. 3. The multicomponent plastic product according to claim 1 or 2, wherein the second semi-crystalline thermoplastic polymer has a melting temperature (Tm) of less than 180°C.

4. 4. The multi-component plastic product of claim 3, wherein the second semi-crystalline thermoplastic polymer has a melting temperature (Tm) of less than 150°C.

5. 5. The multi-component plastic product of claim 4, wherein the second semi-crystalline thermoplastic polymer has a melting temperature (Tm) of less than 120°C.

6. 6. A multicomponent plastic product according to any one of claims 1 to 5, wherein the second semi-crystalline thermoplastic polymer is selected from polylactic acid (PLA), polycaprolactone (PCL), polybutylene adipate terephthalate (PBAT), polyhydroxyalkanoate (PHA), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate (PBA), polyglycolic acid (PGA), ethylene vinyl acetate (EVA), polydioxanone (PDS), polyethylene glycol (PEG), polyethylene oxide (PEO) and copolymers and derivatives thereof.

7. A multicomponent plastic product according to any one of claims 1 to 6, wherein the first semi-crystalline thermoplastic polymer is selected from polyolefins, aliphatic and semi-aromatic polyesters, polyamides, polyurethanes, vinyl polymers, polyether or ester ether copolymers and their derivatives.

8. A multicomponent plastic product according to any one of the preceding claims, wherein the first semi-crystalline thermoplastic polymer is selected from aliphatic and semi-aromatic polyesters and polyamides.

9. 9. A multicomponent plastic product according to claim 8, wherein the first semi-crystalline thermoplastic polymer is selected from PLA, PET or copolymers of PET, PA6 or PA6,6.

10. A multicomponent plastic product according to any one of the preceding claims, wherein the weight ratio of the first thermoplastic material / the second thermoplastic material is between 50 / 50 and 99 / 1.

11. A multi-component plastic product according to any one of claims 1 to 10, wherein the multi-component product is selected from a multi-component filament or a multi-layer plastic product.

12. 12. The multicomponent plastic product according to any one of claims 1 to 11, wherein the multicomponent product is a multicomponent filament and the first thermoplastic material and the second thermoplastic material are arranged in a sheath / core, tipped trilobal, bicomponent trilobal, side-by-side, islands-in-the-sea or segmented pie configuration.

13. A multicomponent plastic product according to any one of claims 1 to 11, wherein the multicomponent product is a multicomponent filament, the first thermoplastic material being a sheath made of the first semi-crystalline thermoplastic polymer and the second thermoplastic material being a core made of the second semi-crystalline thermoplastic polymer and a degrading enzyme.

14. 14. The multi-component plastic product of claim 12 or 13, wherein the multi-component product is a multi-component filament, the first thermoplastic material comprises PLA, and the second thermoplastic material comprises PCL and a PLA degrading enzyme.

15. 14. The multi-component plastic product of claim 12 or 13, wherein the multi-component product is a multi-component filament, the first thermoplastic material comprises PET or a copolymer of PET, and the second thermoplastic material comprises PCL and a PET degrading enzyme.

16. 12. The multi-component plastic product according to any one of claims 1 to 11, wherein the multi-component product is selected from multi-layer plastic films, multi-layer plastic sheets, multi-layer plastic trays, multi-layer plastic bottles, multi-layer packaging, multi-layer profiles and tubes.

17. A method for producing a multi-component plastic product according to any one of claims 1 to 16, comprising the steps of: a. selecting a first thermoplastic material comprising at least 70% by weight of a first semi-crystalline thermoplastic polymer based on a total weight of the first thermoplastic material; b. selecting a degrading enzyme capable of degrading the first semi-crystalline thermoplastic polymer; c) mixing the degradative enzyme with a second semi-crystalline thermoplastic polymer at a temperature at which the second semi-crystalline thermoplastic polymer is partially or completely molten to obtain a second thermoplastic material, the second semi-crystalline thermoplastic polymer having a melting temperature (Tm) lower than the melting temperature (Tm) of the first semi-crystalline thermoplastic polymer; d. co-extrusion or co-injection or extrusion coating said thermoplastic material to obtain a multi-component product; A method comprising:

18. 20. The method of claim 17, wherein the multicomponent plastic product is a multicomponent filament produced by co-extruding the thermoplastic materials.

19. 19. The method of claim 17 or 18, wherein the co-extrusion step is carried out in a co-extruder using a co-extrusion die selected from a sheet die, a flat film die, a pipe or tube die, a profile die.

20. 20. The method according to any one of claims 17 to 19, wherein the degradative enzyme is mixed with the second semi-crystalline thermoplastic polymer in an amount of 0.001 to 30% by weight, based on the total weight of the second thermoplastic material.

21. A method for producing a multicomponent product according to any one of claims 1 to 16, comprising the steps of: a. selecting a first thermoplastic material comprising at least 70% by weight of a first semi-crystalline thermoplastic polymer based on a total weight of the first thermoplastic material; b. selecting a degrading enzyme capable of degrading the first semi-crystalline thermoplastic polymer; c) mixing said degradative enzyme with a second semi-crystalline thermoplastic polymer at a temperature at which said second semi-crystalline thermoplastic polymer is partially or completely molten to obtain a second thermoplastic material; d) processing said thermoplastic materials by co-extrusion, co-injection or extrusion coating at a processing temperature in an extruder where said materials are in a partially or completely molten state to obtain a multi-component product, said processing temperature in said extruder of said second thermoplastic material being lower than said processing temperature in said extruder of said first thermoplastic material; The method includes:

Citation Information

Patent Citations

  • Biodegradable laminate film and agricultural biodegradable film

    JP2000238194A

  • Civil engineering geogrid

    JP2009228377A

  • Polyamide core-sheath composite fiber excellent in hygroscopicity and contact cool feeling and fabric using the same

    JP2016204784A

  • Masterbatch compositions containing high concentrations of biological entities

    JP2018525457A

  • Multilayered molded polyester with barrier property

    WO2008146803A1